Comparison of coarse‐resolution rapid methods for assessing fish passage at riverine barriers: ICE and SNIFFER protocols. (27th September 2018) - Barry, James; Coghlan, Brian; Cullagh, Alan; Kerr, James R.; King, James J.
Abstract: Man‐made barriers have led to river fragmentation, restricting fish migrations to critical habitat. Fragmentation is relevant to the Water Framework and Habitats (Annex II fish) Directives of the European Union. SNIFFER (Water Framework Directive 111) is a United Kingdom‐developed fish passability assessment method with passability scores based on published data describing the physiological abilities of different fish species/life stages. SNIFFER is an objective protocol, but final scores require assessor opinion on specific nonquantified elements. The French ICE fish passability assessment protocol covers a larger number of fish species/life stages and removes the requirement for velocity readings (except in a few situations) and expert opinion with assessors following a decision tree process. In most situations, fewer direct measurements are required for the ICE protocol, and the evaluation process is quicker and simpler. Both protocols utilize a similar passability scoring system (0 = total barrier, 0.3 = high impact, 0.6 = low impact, 1 = no risk). Comparison of outcomes for species categories for both protocols was made in paired comparisons for 112 transversal sections (fish passage routes) recorded at 52 barriers (in‐river structures) of varying complexity in Irish rivers. Overall scores were found to be in high agreement for species groups at impassable (Score 0) and no risk (Score 1) barriers. Protocol agreement dropped significantly for high‐impact (Score 0.3) and low‐impact (Score 0.6) barriers. Results are discussed in the context of barrier passability at the 52 structures examined, primarily in the context of Atlantic salmon ( Salmo salar L.) and of sea lamprey ( Petromyzon marinus L.). In total, 22 of the structures had one or more fishways or fish passage solutions built into them as part of the original design. Both protocols identified substantial problems for sea lamprey and adult salmon at the majority of the fish passage solutions surveyed. The merits and shortcomings of both protocols, for managers assessing fish passability at complex riverine structures, are discussed.